Serum estradiol levels in infertile men with non-obstructive azoospermia - Nader Salama; Saeed Blgozah (Therapeutic Advances in Reproductive Health, 2020)
Purpose: To report the different patterns of estradiol levels in infertile men with non-obstructive azoospermia and correlate these levels with their clinical and laboratory findings. Materials and methods: A retrospective study was launched, and a retrieval of data for infertile men with non-obstructive azoospermia ( n  = 166) and fertile controls ( n  = 40) was performed. The retrieved data included demographics, clinical findings, scrotal duplex, semen analysis, and hormonal assay (testosterone, follicle-stimulating hormone, luteinizing hormone, prolactin, and estradiol). Results: Our findings showed a wide spectrum of estradiol concentrations. The patients were arranged into three groups (high, normal, and low estradiol groups). The normal estradiol group was the most prevalent (71.1%). Testosterone, gonadotrophins, testicular volumes, and the number of patients with jobs in polluted workplaces showed significant differences among the study groups ( p  = 0.001, <0.001, <0.001, and 0.004, respectively). Age, body mass index, varicocele prevalence, prolactin, and smoking habits did not show any significant differences among the groups. Obesity was lacking in the low estradiol group, but it had significantly higher prevalence in the normal ( p  = 0.013) or high group ( p  = 0.023) compared with the controls. Conclusion: Serum estradiol, in infertile men with non-obstructive azoospermia, may be present at different levels. It is recommended that estradiol be measured in infertile men with non-obstructive azoospermia when there is an alteration in testosterone concentration, obesity, a polluted workplace occupation, or before trying hormonal therapy. Extended studies are highly recommended to provide a clear clue whether alterations in estradiol concentrations in men with non-obstructive azoospermia are the cause or a consequence of the condition.